Isolation and characterization of Shiga toxigenic Escherichia coli of animal and bird origin by multiplex polymerase chain reaction - S. Neher (Veterinary World, 2016)
Aim: The purpose of this study was to determine the virulence genes and serotype of Shiga toxin producing Escherichia coli (STEC) strains isolated from animals and birds. Materials and Methods: A total of 226 different samples viz., fecal, intestinal content, rectal swab and heart blood were collected from different clinically affected/healthy animals and birds and were streaked on McConkeys’ lactose agar and eosin methylene blue agar for isolation of E. coli, confirmed by staining characteristics and biochemical tests. By polymerase chain reaction (PCR) all the E. coli isolates were screened for certain virulence genes, viz., Shiga toxin 1 (stx1), stx2 and eae and enterohemolytic (Ehly) phenotype was observed in washed sheep blood agar plate. All the isolated E. coli strains were forwarded to the National Salmonella and Escherichia Centre, Central Research Institute, Kasauli (Himachal Pradesh) for serotyping. Results: Out of 226 samples 138 yielded E. coli. All the isolates were screened for molecular detection of different virulent genes, viz. stx1, stx2 and eae, based on which 36 (26.08%) were identified as STEC. Among those STEC isolates, 15 (41.67%), 14 (38.89%), 1 (2.78%) exhibited eae, stx2, stx1 alone, respectively, whereas 4 (11.11%) and 2 (5.56%) carried both stx1 and stx2, stx2 and eae, respectively. Among the STEC isolates 22 were belonged to 15 different sero-groups, viz., O2, O20, O22, O25, O43, O60, O69, O90, O91, O95, O106, O118, O130, O162 and O170 and others were untypable. Ehly phenotype was observed in 10 (27.78%) the STEC isolates. Conclusion: The present study concluded that STEC could be isolated from both clinically affected as well as healthy animals and birds. Regular monitoring of more samples from animal and bird origin is important to identify natural reservoir of STEC to prevent zoonotic infection.